1985
DOI: 10.1111/j.1432-1033.1985.tb09225.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for multistability in a photobiochemical system

Abstract: The kinetic behavior of a typical Hill reaction catalyzed by thylakoids and using the oxidized form of 2,6-dichloroindophenol (DCPIPox) as the artificial clectron acceptor, is considered. Here, the light absorption process and the reduction of DCPlPox are autocatalytically coupled, leading to the occurrence of rnultiplc steady states with respect to either the acceptor concentration or the incident light intensity. Experimental evidence is prescntcd for both cases and the emergence of autocatalysis is discusse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1986
1986
1992
1992

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…According to the reaction-diffusion theory, the interaction of diffusion transport and nonlinear chemical kinetics can lead to instabilities of a concentration field with the result that initially homogeneous domains develop regional nonuniformities (1,2). The autocatalytic nature of a photobiochemical reaction resulting from the coupling of two intrinsically linear processes-i.e., the reduction of DCIP by thylakoids and the light absorption by the same electron acceptor DCIP-has been demonstrated in a spatially compartmentalized system (25,30). In those studies, the existence of multiple steady states in a single open reactor and of stable asymmetric steady states in coupled open reactors with mutual diffusion through an inert membrane was shown by experimental and numerical methods.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…According to the reaction-diffusion theory, the interaction of diffusion transport and nonlinear chemical kinetics can lead to instabilities of a concentration field with the result that initially homogeneous domains develop regional nonuniformities (1,2). The autocatalytic nature of a photobiochemical reaction resulting from the coupling of two intrinsically linear processes-i.e., the reduction of DCIP by thylakoids and the light absorption by the same electron acceptor DCIP-has been demonstrated in a spatially compartmentalized system (25,30). In those studies, the existence of multiple steady states in a single open reactor and of stable asymmetric steady states in coupled open reactors with mutual diffusion through an inert membrane was shown by experimental and numerical methods.…”
Section: Resultsmentioning
confidence: 98%
“…Similar one-dimensional patterns were also observed when red (cutoffofradiation <580 nm; wavelengths ofphotosystem II excitation) and infrared filters were utilized together. The chlorophyll concentration and light intensity determinations were done as reported (25).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This latter transition emerges when the non-linear properties of the implicated reactions are coupled to diffusion under welldefined boundary conditions. It has been suggested that the coupling ofthe non-linear photosynthetic reduction ofan electron acceptor [23] to diffusion in the presence of a gradient was the underlying mechanism of the symmetry change of the electron acceptor in a photobiochemical system [13].…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical processes taking place in each cell are identical to those described by Breton et ai. 29 ,30 and the evolution of the substrate is governed by Eq. (1).…”
Section: Introductionmentioning
confidence: 99%